Penerapan Latihan Fisik Kombinasi Beban Internal Dan Beban Eksternal Dominan Terhadap Peningkatan Kemampuan Koordinasi Tendangan Maegeri Denganmawasi Geri Pada Atlet Ingkanas Ranting UNM - Dahlan Dahlan; Amri Rahman (Seminar Nasional LP2M UNM, 2019)
The Implementation of Physical Exercise Combination of Internal and External Loads Dominant Power Improvement of Maegeri Kick Coordination With Gaw Mawasi At UNM Branch Inglower Athletes. This type of research is a true experimental descriptive. The sample used in this research is the athletes of UNM karate ingkanas. The data analysis technique used is the average difference test analysis technique, namely the t test at a significant level of 95% or α = 0.05. The results showed that: (1) There was an increase in the ability of maegeri and mawashi geri kicks through the application of dominant internal weight training in athletes in the martial arts branch of Ingkanas branch UNM with the value of t count (to) = 23.482> T.Table = 2.1448 with a high level probability (P) = 0.000 <α = 0.05). (2) There is an increase in the ability of maegeri and mawashi geri kicks through the application of dominant external weight training in athletes in the martial arts branch of the Ingkanas branch UNM karate, obtained the value of T count (to) = 11.993> T. Table = 2.1448 with a probability level (P) = 0,000 ˂ α = 0.05). (3) There is a difference in the increasing ability of maegeri and mawashi geri kicks through the application of dominant internal weight training and dominant external weight training in athletes in the karate martial arts Ingkanas twigs UNM obtained t count value (to) = 2.641 <T.Table = 2.048 with a level probability (P) = 0.013 <α = 0.05), the average difference (mean) for the internal load group is 17.80, and for the external load group is 20.60 meaning that external weight training gives a better effect on increasing the ability to coordinate the kick of the maegeri and Mawashi Geri in athletes remember the UNM twigs compared with internal weight training.